1977
DOI: 10.1246/bcsj.50.473
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Chemiluminescence of Lucigenin. II. The Charge-transfer Structure of Lucigenin and Reduction of 10,10′-Dimethyl-9,9′-biacridinium Dication by Electron Transfer from Nucleophiles

Abstract: Lucigenin (10,10′-dimethyl-9,9′-biacridinium dinitrate, DBA2+2NO3−) was found to be a CT complex between DBA2+ and NO3−. In the reaction of lucigenin with several nucleophiles in the absence of molecular oxygen or oxidizing agents the following four types of products were obtained, depending upon the relative power of the nucleophiles to donate electrons to DBA2+: (1) salts of DBA2+ (DBA2+2X−) which are the CT complex between DBA2+ and the nucleophiles, such as Cl−, Br−, SCN−, and I−, (2) the cation radical DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…It can be known from Fig. 2 that the main reason for generation of the ECL of lucigenin is due to the reaction between lucigenin and the electrogenerated oxygen radical [1,2]. Our preliminary experiments showed that clonazepam did not give ECL emission on the TNTs/chitosan film-modified electrode, while it could greatly enhance the ECL intensity of luciginin in KCl solution on the TNTs/chitosan film-modified electrode.…”
Section: Ecl Behaviors Of Lucigenin At Tnts/chitosan Composite Modifimentioning
confidence: 63%
See 1 more Smart Citation
“…It can be known from Fig. 2 that the main reason for generation of the ECL of lucigenin is due to the reaction between lucigenin and the electrogenerated oxygen radical [1,2]. Our preliminary experiments showed that clonazepam did not give ECL emission on the TNTs/chitosan film-modified electrode, while it could greatly enhance the ECL intensity of luciginin in KCl solution on the TNTs/chitosan film-modified electrode.…”
Section: Ecl Behaviors Of Lucigenin At Tnts/chitosan Composite Modifimentioning
confidence: 63%
“…Thereby, it is becoming a powerful detection method in recent years. Lucigenin (N,Ndimethyl-9,9 -biacrid-inium dinitrate) is an important ECL reagent, and considerable studies with regard to its chemiluminescence (CL) mechanism have been published [1,2]. However, owing to its low sensitivity and easy electrode fouling, less attention has been paid to the ECL of lucigenin than to its chemiluminescent.…”
Section: Introductionmentioning
confidence: 99%
“…A new ECL peak was found at À0.03 V in KI solution upon reversal of the potential scan from À1.6 V. As intensity of this ECL peak was too weak to measure its spectrum, it was impossible to explain the formation mechanism at this moment. The slight difference in ECL intensity in different electrolytes and the emergence of new ECL peak in KI solution were probably due to the formation of charge- transfer complex between lucigenin and halogen ions [5], which might have certain effect on the generation of intermediate.…”
Section: Electrochemical and Ecl Of Lucigenin In Neutral Solution Undmentioning
confidence: 99%
“…The most important ECL reactions in the analytical and bioanalytical fields include luminol, ruthenium (II) tris (2,2 0 -bipyridine), and acridinium ester [2]. Lucigenin (N,N 0 -dimethyl-9,9 0 -biacridinium dinitrate) is one kind of acridinium ester and numerous studies [3][4][5][6] concerning the mechanism of lucigenin chemiluminescence (CL) have been carried out since it was reported in 1935 by Gleu and Petsch [7]. As ECL is advantageous over CL, the ECL and electrochemistry of lucigenin have already been investigated in aqueous and non-aqueous media at different electrodes [8][9][10][11][12] and the mechanism of ECL has also been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of charge-transfer (CT) complexes between the biacridinium cation and various anions was also investigated with respect to the lucigenin CL reaction. 18 Lucigenin is known to react with the reductants14, such as ascorbic acid, glucose, urea and iron(II), to form intense CL light over a wavelength range of 420 -510 nm in the same manner as an oxidant, such as hydrogen peroxide. 19 On the other hand, flow injection analysis (FIA) is one of the simplest approaches to the automation of chemical analysis, and is being applied to a wide variety of analytical fields.…”
mentioning
confidence: 99%